PERAN ORANG TUA DALAM MENDUKUNG PEMBENTUKAN AKHLAK TERPUJI SISWA DI MI NURUL ULUM KECAMATAN TIRIS KABUPATEN PROBOLINGGO - Nanik Yuliana; Devy Habibi Muhammad (LPPM STAI Muhammadiyah Probolinggo, 2026)
This research method uses qualitative descriptive research. The data source used in this research used random sampling, totaling 6 parents in Andungsari Village, Andungsari District. The emergence of symptoms of a decline in morals that occur among young children can be seen in children's poor behavior and bad words spoken by young children. This research aims to find out the role of parents in the formation of morals in early childhood. Based on the results of research on the role of parents in forming children's morals, the results obtained are: parents have provided education in the form of moral and religious values, given examples of good behavior and speech, carried out habits with their children, some parents have also given sanctions, namely in the form of light punishments which have a deterrent effect on children. Apart from education in the family, factors that can influence the formation of morals are the school environment and community environment. From the results of interviews with parents, there were children who liked to talk dirty, this was due to the influence of friends when they were outside the house. On the other hand, there are also children who behave less well at home, but children are more reluctant at school because they feel afraid of teachers and people around them.